2022
DOI: 10.1002/tox.23483
|View full text |Cite
|
Sign up to set email alerts
|

Hexavalent chromium induces hepatocyte apoptosis via regulation of apoptosis signal‐regulating kinase 1/c‐Jun amino‐terminal kinase signaling

Abstract: With the spread of hexavalent chromium (Cr(VI)) contamination, Cr(VI)-induced hepatotoxicity has attracted increasing attention in recent years. To date, however, the exact mechanism of Cr(VI) toxicity remains unclear. In this study, we investigated the role of apoptosis signal-regulating kinase 1 (ASK1)/c-Jun aminoterminal kinase (JNK) in Cr(VI)-induced hepatic toxicity and the possible related mechanisms. AML-12 hepatocyte cell-lines were treated with 0, 1, 4, and 16 μmol/Lof Cr(VI) with or without GS-444271… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…There is now sufficient experimental evidence that chromium triggers apoptosis and promotes inflammation by inhibiting the deacetylation of SIRT1 [ 43 ], which stands for sirtuin (silent mating-type information regulation 2 homolog) as a member of a protein family involved in signaling metabolic regulation. Other, more recent mechanistic proposals focus on signaling processes [ 45 ]. For instance, downregulation of Nrf2 signaling may contribute to hepatocyte apoptosis and ROS-dependent liver injury elicited by Cr 6+ , in addition to ASK1/JNK-signaling activity, which was upregulated.…”
Section: Chromiummentioning
confidence: 99%
“…There is now sufficient experimental evidence that chromium triggers apoptosis and promotes inflammation by inhibiting the deacetylation of SIRT1 [ 43 ], which stands for sirtuin (silent mating-type information regulation 2 homolog) as a member of a protein family involved in signaling metabolic regulation. Other, more recent mechanistic proposals focus on signaling processes [ 45 ]. For instance, downregulation of Nrf2 signaling may contribute to hepatocyte apoptosis and ROS-dependent liver injury elicited by Cr 6+ , in addition to ASK1/JNK-signaling activity, which was upregulated.…”
Section: Chromiummentioning
confidence: 99%
“…Cr(VI) in the environment can be absorbed by the human body through the digestive tract and respiratory system, and the liver is the main target organ for Cr(VI) accumulation. When the absorbed Cr(VI) enters hepatocytes, it is reduced to low‐valent Cr and generates a large amount of ROS, thereby activating the ASK1–JNK signaling pathway and leading to hepatocyte apoptosis 71 …”
Section: Apoptosis Signal‐regulated Kinase 1 and Liver Diseasementioning
confidence: 99%
“…When the absorbed Cr(VI) enters hepatocytes, it is reduced to low-valent Cr and generates a large amount of ROS, thereby activating the ASK1-JNK signaling pathway and leading to hepatocyte apoptosis. 71 Developing drugs targeting apoptosis signal-regulated kinase 1 as effective targets for liver diseases Previous studies have found that direct use of small-molecule inhibitors of p38 or JNK to prevent p38-mediated and JNK-mediated diseases was generally unsuccessful, as targeted disruption of the p38a gene results in severe defects in placental development in mice, resulting in increased homozygous embryos mortality. Additionally, loss of any MAPK pathway members coding genes leads to defects in mouse osteoblast differentiation.…”
Section: Apoptosis Signal-regulated Kinase 1 and Viral Hepatitis Cmentioning
confidence: 99%